Prevalence of Hypertension and Its Associated Risk Factors among 34,111 HAART Naïve HIV-Infected Adults in Dar es Salaam, Tanzania - Marina Njelekela; Alfa Muhihi; Akum Aveika; Donna Spiegelman; Claudia Hawkins; Catharina Armstrong; Enju Liu; James Okuma; Guerino Chalamila; Sylvia Kaaya; Ferdinand Mugusi; Wafaie Fawzi (International Journal of Hypertension)
Background. Elevated blood pressure has been reported among treatment naïve HIV-infected patients. We investigated prevalence of hypertension and its associated risk factors in a HAART naïve HIV-infected population in Dar es Salaam, Tanzania. Methods. A cross-sectional analysis was conducted among HAART naïve HIV-infected patients. Hypertension was defined as systolic blood pressure (SBP) ≥ 140 mmHg and/or diastolic blood pressure (DBP) ≥ 90 mmHg. Overweight and obesity were defined as body mass index (BMI) between 25.0–29.9 kg/m2 and ≥30 kg/m2, respectively. We used relative risks to examine factors associated with hypertension. Results. Prevalence of hypertension was found to be 12.5%. After adjusting for possible confounders, risk of hypertension was 10% more in male than female patients. Patients aged ≥50 years had more than 2-fold increased risk for hypertension compared to 30–39-years-old patients. Overweight and obesity were associated with 51% and 94% increased risk for hypertension compared to normal weight patients. Low CD4+ T-cell count, advanced WHO clinical disease stage, and history of TB were associated with 10%, 42%, and 14% decreased risk for hypertension. Conclusions. Older age, male gender, and overweight/obesity were associated with hypertension. Immune suppression and history of TB were associated with lower risk for hypertension. HIV treatment programs should screen and manage hypertension even in HAART naïve individuals.